Identification of Pseudomonas fluorescens using different biochemical tests - Bikram Nepali; Sabin Bhattarai; Jiban Shrestha (International Journal of Applied Biology, 2018)
Pseudomonas fluorescens not only enhances the plant growth but also controls the fungal pathogens by production of anti fungal metabolites. The objective of this experiment was to identify P. fluorescens using different biochemical tests. This research was carried out in Plant Pathology Laboratory at Agriculture and Forestry University (AFU), Rampur, Chitwan, Nepal. The result of this experiment indicated that P.  fluorescens gave positive result for Catalase test, Gelatin liquefaction, Fluorescent pigment and Oxidase test but negative result for starch hydrolysis test. The colony of P. fluorescens was maximum in maize seed than that of rice seed after two hours of inoculation, whereas higher number of colony was found in rice seed than that of maize seed after twenty four hours of seed inoculation. This findings is useful for identifying colony of P. fluorescens  per seed which is necessary for better seedling growth and effective biological control of pathogens.